P1234 Impact of hysterectomy after chemoradiation therapy for locally advanced cervical cancer. (1st November 2019) - Ouldamer, L; Faussat, C; Bendifallah, S; Touboul, C; Collinet, P; Coutant, C; Akladios, C; Lavoué, V; Bolze, PA; Huchon, C; Bricou, A; Canlorbe, G; et al.
Abstract : Introduction/Background: Standard of care worldwide of locally advanced cancer tend to be non surgical (chemoradiation therapy) with no certainty if this attitude improves survival or not. Therefore, it is important to assess the value of hysterectomy in addition to chemoradiation therapy in this context. The sole randomized controlled trial (Morice 2012) designed to answer a similar question was closed early due to poor accrual and included 61 women, reported no difference in overall and recurrence-free survival between chemoradiation therapy and hysterectomy versus chemoradiotherapy alone. Methodology: Data from 1, 963 patients with cervical cancer were collected retrospectively from1 January 2000 to 31 December 2016, from the FRANCOGYN database, pooling data from 12 centres. Survival was determined using the Kaplan-Meier method. Univariate and multivariate analyses were performed to define prognostic factors of survival. Patients included had IB2 to IIB FIGO stage. Results: 739 were included with a mean age of 53.5 years (±13.5). 634 women had available data of imaging after chemoradiotherapy. Management according to the presence of residue on imaging is presented on figure 1. 376 women had hysterectomy. There were significant differences for the 5-year Overall Survival (OS) rates between women who underwent hysterectomy and women who did not (p<0.0001). Salvage hysterectomy was an independent negative predictive factor of OS (HR=0.27 (95%CI, 0.16–0.45), p<0.0001). There were also significant differences for the 5-year Disease-Free Survival (DFS) rates between the two groups (p<0.0001). Salvage hysterectomy was an independent negative predictive factor of DFS (HR=0.45 (95%CI, 0.31–0.66), p<0.0001). Conclusion: A potential positive effect of hysterectomy after chemoradiation therapy for stage IB2 to IIB cervical cancer should be considered. Disclosure: Nothing to disclose.